STUDENTS TO THINK LOGICALLY THROUGH DIDACTIC GAMES - Umarova, Gozalkhon; Karaboeyeva, Pokizakhan (University Research Base, 2024)
Mathematics is to develop students' abilities and interests based on the formation of students' intellectual thinking. Therefore, the development of the methodology of conveying the concept of arithmetic operations and methods of calculation in elementary grades includes the development of the skills and abilities of students to form the basic concepts of elementary mathematics and to apply them in practice. From this point of view in the educational process, teaching mathematical problems, including methods of solving problems of vital importance, based on their accumulated experience, and their application, has its own characteristics, which are used in education use in revealing the content and essence of the studied concepts, teaching in interaction and combined with the experience of students' practical activities are considered to be urgent issues. The development and implementation of these methods serve to increase the quality and effectiveness of teaching. One of the main goals of teaching mathematics in primary education is the development of students' abilities and interests based on the formation of students' intellectual thinking. Therefore, the development of the methodology of conveying the concept of arithmetic operations and the methods of calculation in primary grades involves the development of the skills and abilities of students to form the basic concepts of elementary mathematics and to apply them in practice.